(untitled) (Annals of the University of Bucharest. Philosophy Series, 2024)
The development of Islam in Azerbaijan is a dynamic process shaped by both historical and contemporary events. The policy of state atheism during the Soviet period contributed by strengthening the role of religion. The article aims to highlight the role of Islam and its affirmation as a viable political project and as a resonator of everything happening in Azerbaijan. Alongside the historical approach an anthropological one has been applied – open to more qualitative studies and sensitive to internal differences, especially towards details usually treated as insignificant, but important for the overall analysis of religion. The ending summarizes how the perception of Islam is transformed not only as social phenomenon, but also as a factor of political change.